The effect of special exercises on some motor manifestations and learning to perform throwing catches from the high back and side in free wrestling for young people (Journal of the College of Basic Education, 2022)
The aim of the study was to identify the effect of special exercises prepared in some motor aspects and to learn the performance of tow Skills throwing from the high and lateral back of young wrestlers. The researchers followed the experimental research method by designing the two experimental control and experimental groups of pre- and post- 18-20 years of age, continuing in the Salman School for wrestling in the province of Maysan for the Mathematical Mark (2017/2018) of the 10 weights of the system adopted in wrestling competitions according to international law (57, 61, 65, 70, 74, 79). , 85, 92, 97, 120) was a brother (12) wrestlers (75%) of the parent community. Special exercise vocabulary was applied to the experimental group of (6) wrestlers for a period of (12) weeks and a rate of (3) units per week for each day Saturday, Monday and Wednesday, This application began on Saturday, 24/2/2018 and ended on Wednesday, 16/5/2018, bringing the number of units (24) educational units, each holding (12) units and the wrestlers of the control group have engaged in exercises with them in The school and the researchers were satisfied with their attendance. After the study was completed, the results were processed using the SPSS system. The researchers concluded that learning with special exercises helps young wrestlers to control the amount of muscular contractions of the locomotives, improve the motor mobility of the two movements, improve the performance of the high-end throwing, Grab the backhand and excel in this improvement on young wrestlers who learn without it.